Correlation between family function and self-management abilities in patients with metabolic dysfunction-associated steatotic liver disease - Yueying Zhu; Ru Chen; Hang Han; Xiuli Lin; Meichun Shu (Journal of Health, Population and Nutrition)
Abstract Objective This study aims to evaluate the current state of family function and self-management abilities in patients with metabolic dysfunction-associated steatotic liver disease (MASLD) and analyze the correlation between the two. Methods Baseline data were collected from 243 patients with MASLD, utilizing the Family Care Index and Self-Management Scale. Multiple linear regression analysis was employed to assess factors influencing self-management in these patients. Results The mean score on the Self-Management Scale for the 243 MASLD patients was (92.74 ± 17.22), while the Family Function Scale score was (5.99 ± 1.61). Spearman correlation analysis indicated a positive correlation between family function and scores in disease prevention and control, daily living, disease knowledge, psychological awareness, and unhealthy lifestyle (rs = 0.220, 0.198, 0.227, 0.149, 0.257, 0.266; P < 0.05). Multiple linear regression analysis identified several factors affecting self-management abilities in MASLD patients: smoking history (β’=-0.317), marital status (β’=0.292), family function (β’=0.279), educational level (β’=0.157), severity of fatty liver (β’=0.144), and gender (β’=-0.126) (P < 0.05). Conclusion A significant proportion of MASLD patients exhibit family function impairment, which severely affects their self-management abilities. Interventions aimed at improving family function in MASLD patients are necessary to enhance self-management behaviors and improve disease prognosis.